2010
DOI: 10.1007/s12010-010-8965-5
|View full text |Cite
|
Sign up to set email alerts
|

Ball Milling Pretreatment of Corn Stover for Enhancing the Efficiency of Enzymatic Hydrolysis

Abstract: Ethanol can be produced from lignocellulosic biomass with the usage of ball milling pretreatment followed by enzymatic hydrolysis and fermentation. The sugar yields from lignocellulosic feed stocks are critical parameters for ethanol production process. The research results from this paper indicated that the yields of glucose and xylose were improved by adding any of the following dilute chemical reagents: H(2)SO(4), HCl, HNO(3), CH(3)COOH, HCOOH, H(3)PO(4), and NaOH, KOH, Ca(OH)(2), NH(3)·H(2)O in the ball mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 16 publications
0
60
0
2
Order By: Relevance
“…Various pretreatment processes of lignocellulosic feedstock [14] Physical pretreatment consists of mechanical disruption of lignocelluloses, which is an environmentally friendly process. This process increases the surface area of biomass and decreases the crystallinity of cellulose, but it does not cause an expensive mass loss [25]. Irradiation using gamma rays, electron rays and microwaves are other physical methods to beak the structure of lignocelluloses.…”
Section: Pretreatment Type Examplementioning
confidence: 99%
See 3 more Smart Citations
“…Various pretreatment processes of lignocellulosic feedstock [14] Physical pretreatment consists of mechanical disruption of lignocelluloses, which is an environmentally friendly process. This process increases the surface area of biomass and decreases the crystallinity of cellulose, but it does not cause an expensive mass loss [25]. Irradiation using gamma rays, electron rays and microwaves are other physical methods to beak the structure of lignocelluloses.…”
Section: Pretreatment Type Examplementioning
confidence: 99%
“…The oxidative biodegradation of lignin by white-rot fungi has been widely studied in the past [36]. The main advantages of biological pretreatment are low energy input, no chemical requirement, mild environmental conditions and environmentally friendly working manner [25]. However, the biological pretreatment processes usually need a long retention time and have a low yield.…”
Section: Pretreatment Type Examplementioning
confidence: 99%
See 2 more Smart Citations
“…Such techniques are designed to bring about an increase in accessible surface area, which in turn leads to an enhancement in enzyme digestion rate and yield. Previous studies have shown that dry ball-milling of untreated biomass can be effective in this regard [14,15] although this may be a lengthy and energy-intensive operation [16,17]. Wet-state mechanical disintegration is more advantageous in that it avoids the energy expense of drying and can be integrated into a sequence of other wet processing steps, either as a pretreatment [18,19] or combined with simultaneous enzymatic treatment [20,21].…”
Section: Introductionmentioning
confidence: 99%